CICLO RUTA AGROTURÍSTICA DEL CERRO COLAMBO DE LA PARROQUIA PURUNÚMA, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - CEVALLOS BRICEÑO, NIXON ALEXANDER (2018)
Agrotourism is a form of tourism that has been developed in rural areas and has grown enormously in recent decades. However, in many of the rural sectors it has not been possible to take advantage of and implement this type of tourism, since they lack the basic tourist infrastructure for the reception of visitors. Even with these limitations, agrotourism has in its favor, the recognition of local agronomic practices, which in turn helps to highlight the culture and traditions of the places where it is implemented. Gonzanamá canton, and Purunúma parish stand out for their great wealth in the field of agriculture and livestock, making it the ideal place for the implementation of this tourism. For this reason the proposal for a new and novel tourism product was carried out in this research, which has as its general objective: To develop an agrotourism route for the Cerro Colambo of the Purunúma parish, Gonzanamá canton in the province of Loja; from which three specific objectives that will allow the fulfillment of the research are derived. The first objective is to "Carry out a tourist diagnosis of the Purunúma and Gonzanamá parishes"; using the analytical method that allows to know in a disaggregated way the characteristics of the places to be studied. To this end, it was supported by the methodology of the local tourist diagnosis of Carla Ricaurte, based on the techniques of direct observation and interviews with various key actors; the SWOT matrix, allowed to determine the internal and external factors of the investigated area; the MARPP technique, which allowed consulting directly with the beneficiaries of the project, as well as determining the socioeconomic reality of the sector, based on surveys. The development of the second objective, "Design the Agrotourism Cycle-route of the Cerro Colambo of the Purunúma parish of Gonzanamá canton in the province of Loja"; the descriptive method was applied to detail each of the points of the proposed cycle-route that were carried out using the global georeferencing technique; and also with the help of the tourism inventory cards of the Ministry of Tourism of Ecuador. For this purpose, a collection of all the data obtained from the diagnosis was made and with this the cycle-route was proposed, which bears the name: Cerro Colambo Agrotourism Cycle-route; and the slogan: "Come and meet the world of agriculture from your bike". The proposed route also includes an itinerary with its respective script; application of signage and promotional strategies and dissemination of the tourist product. 5 Finally, the third objective: "Socialize the results obtained during the implementation of the agro-tourism cycle of Cerro Colambo"; It was carried out through a socialization workshop with authorities and the population of the study areas, where doubts were solved and recommendations were made about the proposal of the agrotourism cycle-route, all this from the MARPP method, for analysis of rural contexts . As conclusions, it stands out that the approach and design of the agro-tourism cycle of the Cerro Colambo, is a contribution for the conservation and improvement of the attractions of the region. In addition, the study area has basic infrastructure for the reception and attention of future visitors. The recommendations are directed to the local authorities, since it is proposed to support the ideas and undertakings of its inhabitants, because often the ideas are not taken into account due to lack of investment and support from their authorities.